Assembly of the mitochondrial genome of the hydrothermal vent crab Segonzacia mesatlantica and detection of potential nuclear pseudogenes. Issue 1 (1st January 2017) - Mandon, Perrine; Aznar-Cormano, Laetitia; Hourdez, Stéphane; Samadi, Sarah
Abstract: We assembled the mitogenome of the Bythograeid crab Segonzacia mesatlantica, using long-range amplification of the mitochondrial genome. The mitogenome is 15, 521 base pair long (33.8% A, 21.7% C, 10.5% G, 34% T) with 13 protein-coding genes, 2 ribosomal RNA genes, 22 transfer RNAs, and a 624 bp AT-rich region. The gene arrangement is similar to other Brachyuran species. A whole genome shotgun sequencing approach revealed the presence of mitochondrial pseudogenes in the nuclear genome. This fifth mitogenome for a species of Bythograeidae should help resolve the puzzling question of the evolutionary origin of a family limited to deep-sea hydrothermal vents.